Carbon nanotube amorphous carbon composites - Li, Keke (2009)
This project focuses mainly on the field emission properties of multi-walled carbon nanotube (MWNT) films coated with a thin layer of diamond like amorphous carbon (DLC) film. The vibrational motions of the MWNT samples, DLC coated MWNTs and annealed samples were characterized using Raman Spectroscopy. The synthesized MWNTs have a graphite phase G-band at ~1588.64cm-1, and there are various D-peak to G-peak intensity ratios depending on the geometry of the MWNTs. The DLC coating on MWNTs were found to shift the peak away from the nano-crystalline graphite structure of MWNTs. The field emission performance of MWNT films depend on the length of the tubes, diameter and the density. The 2.25nm DLC coated MWNT film requires smaller voltage applied at the defined turn-on current than the uncoated sample. DLC coated MWNT samples also exhibit higher stability in the 1 hour lifetime test of the emission current density.